Abrupt vegetation and environmental change since the MIS 2: A unique paleorecord from Slovakia (Central Europe). (15th February 2020) - Šolcová, Anna; Jamrichová, Eva; Horsák, Michal; Pařil, Petr; Petr, Libor; Heiri, Oliver; Květoň, Jiří; Křížek, Marek; Hartvich, Filip; Hájek, Michal; Hájková, Petra
Abstract: Research on past abrupt climate change and linked biotic response is essential for understanding of the future development of biota under changing climatic conditions, which, in turn, is necessary for adequate progress in ecosystem management and nature conservation. The present study presents the first comprehensive reconstruction of local and regional environment at the Western Carpathian/Pannonian Basin border, including a first chironomid-based paleoclimate reconstruction and δ 18 O and δ 13 C records from travertine, to investigate abrupt biota and climate shifts since the Marine Isotope Stage (MIS) 2. A range of biotic and abiotic proxy data in organic-calcareous sediment sequence were analysed using a multi-proxy approach to produce a detailed reconstruction of past ecosystem conditions. The results illustrate that the most prominent abrupt change in the local environment occurred directly at the MIS 2/MIS 1 transition at 14, 560 cal BP as a consequence of increased precipitation and an increase in reconstructed mean July temperature by ∼2.2 °C. Abrupt changes in local environment during the early Holocene were closely linked to travertine precipitation rate around thermal springs and thus indirectly to the climate until the arrival of the Late Neolithics around 6400 cal BP. Regional vegetation response (derived from pollen data) to the climatic fluctuations lagged, with the most prominent changes around 14, 410 cal BP and 10, 140 cal BP. Our data suggest the presence of a steppe-tundra ecosystem with evidence for low amounts of temperate broadleaf trees during the MIS 2, indicating close proximity to their northern glacial refugium. We demonstrate the ability of δ 18 O and δ 13 C stable isotope record from travertine to reflect abrupt climatic and environmental changes. The study provides evidence about benefits using travertine deposits coupled with high-resolution paleoecological data to investigate past biotic and abiotic responses to abrupt climate change. Highlights: First high-resolution paleoecological record from the Pannonian Basin dating back to MIS 2 using calcareous sediments. The most prominent abrupt change in the local environment occurred at the MIS 2/MIS 1 transition. Abrupt Holocene environmental shifts in the local environment were driven by the change in travertine precipitation rates. Human activities impacted the local environment beginning ∼6400 cal BP. δ 18 O and δ 13 C from travertine reflect abrupt climatic and environmental changes.